Kualitas Jaringan Operator Selular Coverage Indoor dan Outdoor di Lingkungan Universitas Warmadewa - I Made Sastra Dwikiarta; I Putu Yudi Prabhadika; Ida Ayu Rosa Dewinta (Lembaga Penelitian, Universitas Warmadewa, 2024)
Telecommunications technology is growing rapidly, and telecommunications providers are now in the 5G technology phase. Providing very fast speed and data transfer. However, in the development of cellular technology in Indonesia, especially in Bali, the distribution of provider signal coverage areas is not evenly distributed. Although many BTS (Base Transceiver Station) have been scattered and built in the Denpasar city area, there are still locations that are not well covered. In this study the location chosen was the campus area at Warmadewa University. The method used was survey and sample interviews among students, lecturers, and staff. The number of data samples is 100 people. The survey results obtained are the findings of the signal coverage of Telkomsel, Indosat, XL-Axiata providers including coverage ranging from very poor to very good, while the Smartfren and 3 providers include good and very good signal coverage received in the Warmadewa University area. The use of phone calls (pulses) is rarely used because data packages are more flexible and efficient, the selection of calls (pulses) is usually used when urgent conditions.